The Aggregation and Neurotoxicity of TDP-43 and Its ALS-Associated 25 kDa Fragment Are Differentially Affected by Molecular Chaperones in Drosophila. - Gregory, J.M.; Barros, T.P.; Meehan, S.; Dobson, C.M.; Luheshi, L.M. (PLoS ONE, 2012)
Almost all cases of sporadic amyotrophic lateral sclerosis (ALS), and some cases of the familial form, are characterised by the deposition of TDP-43, a member of a family of heteronuclear ribonucleoproteins (hnRNP). Although protein misfolding and deposition is thought to be a causative feature of many of the most prevalent neurodegenerative diseases, a link between TDP-43 aggregation and the dysfunction of motor neurons has yet to be established, despite many correlative neuropathological studies. We have investigated this relationship in the present study by probing the effect of altering TDP-43 aggregation behaviour in vivo by modulating the levels of molecular chaperones in a Drosophila model. More specifically, we quantify the effect of either pharmacological upregulation of the heat shock response or specific genetic upregulation of a small heat shock protein, CG14207, on the neurotoxicity of both TDP-43 and of its disease associated 25 kDa fragment (TDP-25) in a Drosophila model. Inhibition of the aggregation of TDP-43 by either method results in a partial reduction of its neurotoxic effects on both photoreceptor and motor neurons, whereas inhibition of the aggregation of TDP-25 results not only in a complete suppression of its toxicity but also its clearance from the brain in both neuronal subtypes studied. The results demonstrate, therefore, that aggregation plays a crucial role in mediating the neurotoxic effects of both full length and truncated TDP-43, and furthermore reveal that the in vivo propensity of these two proteins to aggregate and their susceptibility to molecular chaperone mediated clearance are quite distinct.